Evaluasi Kinerja Persimpangan Tak Bersinyal Menggunakan Metode PKJI 2014 - Fieri Rinaldo; Felly Misdalena; Galuh Pramita (Jurnal Konstruksi, 2025)
Urban development and rapid population growth have led to an increase in traffic volume on major roads, including the intersection of Airan Raya Street and Jatimulyo. This intersection serves as an alternative route to Metro City and is one of the key links between Bandar Lampung City and South Lampung Regency. Due to the high frequency of vehicles passing through this location, traffic congestion often occurs. The dense traffic flow affects road performance and increases the risk of both accidents and congestion. This study aims to evaluate the performance of the intersection using the PKJI 2014 Method, which takes into account factors such as capacity, degree of saturation, delay, and level of service. To determine the peak traffic volume, a traffic survey was conducted over three days — Saturday, May 10; Thursday, May 15; and Monday, May 19, 2025. Data evaluation was performed using PKJI 2014 analysis techniques. The results show that on Saturday, May 10, between 07:00–08:00, the highest traffic flow occurred, amounting to 5,938 vehicles per hour (equivalent to 2,402.2 seconds per hour after conversion). The degree of saturation (DS) was 0.8836, indicating that the intersection’s capacity needs to be reassessed to prevent more severe congestion. The level of service was categorized as C (moderate) with an average delay of 15.2298 seconds/skr and a queue probability (QP) ranging from 31.3410% to 61.8522%. This study provides a foundation for policy formulation and traffic engineering strategies at unsignalized intersections with high traffic density, supporting efforts to improve road performance and reduce congestion.